Time-Resolved Particle Image Velocimetry Measurements and Proper Orthogonal Decomposition Analysis of Unsteady Flow in a Centrifugal Impeller Passage - Chen, Bo; Li, Xiaojun; Zhu, Zuchao (Frontiers in Energy Research, 2022)
Time-resolved particle image velocimetry (TR-PIV) measurements were conducted to analyze the unsteady flow field developing in a centrifugal pump. The flow structures in the impeller passage under different flow rates were investigated. The overall statistical characteristics of the flow were obtained with the study of relative phase-averaged flow field, phase-averaged turbulent kinetic energy (TKE), and the analysis of frequency. Through the study of the first few proper orthogonal decomposition (POD) modes of the flow field, the coherent flow structures under several flow rates were revealed, consequently, the flow fields were reconstructed by the POD modes. Results show that the main flow structures could be reflected by the first few modes of the flow field: when the fluid follows the blade contour well, the first few modes corresponded to the “jet-wake” structures; when the large-scale flow structures appear in the passage, the 1st and 2nd modes were associated in pairs and corresponded to the stall cells, the 3rd and 4th modes corresponded to the “jet-wake” structures, and the 5th and 6th modes corresponded to the passage vortexes or the “jet-wake” structures (for the extreme part-load conditions). The flow structures that were reflected by the first few modes change as the decrease of flow rate, especially, at the extreme part-load condition, not only the shapes of the flow structures changed, but also the flow direction is reversed. This indicates that the generation mechanism of turbulent kinetic energy in the flow passage changed at the extreme part-load conditions.